Changes in texture and lignin during different developmental stages of mulberries and transcriptome analysis - WANG Binbin; DAI Xianglong; DU Kaiqun; SHEN Zixin; WANG Hui; GAO Yanxia (Guoshu xuebao)
[Objective] Mulberry (Fructus mori), as a typical climacteric fruit, has been extensively studied in areas such as health product development, fruit wine fermentation, analysis of nutritional indicators, identification of aroma components, and postharvest preservation. With the advancement and cost reduction of high-throughput sequencing technologies, transcriptomics and metabolomics have been applied to explore the molecular mechanisms of mulberry ripening and softening. However, there are no reports on the correlation between texture, lignin, and key genes in related pathways during the ripening process of the berry. This study aimed to investigate the changes in texture, lignin, and other indicators during mulberry ripening and softening, analyze transcriptomic data, and identify key factors influencing the ripening and softening process of the berry. [Methods] The new mulberry variety Anshen was used as the test material. The berries were collected at three developmental stages: 20 days after flowering (MGF), 35 days after flowering (MRF), and 45 days after flowering (MBF). The texture indicators (hardness, adhesiveness, cohesiveness, elasticity, gumminess, and chewiness) were measured using a texture analyzer, lignin content was determined using the concentrated sulfuric acid method, and transcriptome sequencing was performed. The QRT-PCR experiments were conducted, and redundancy analysis (RDA) was used to analyze the correlation between lignin, berry texture, and lignin biosynthesis-related genes, as well as to evaluate the relationships among various factors. [Results] As the berries ripened and softened, their hardness gradually decreased, ranging from 3.00 to 50.64 N, while elasticity gradually increased, ranging from 1.86 to 4.41 mm. The gumminess and chewiness gradually decreased, with no significant difference in chewiness between the green berry and red berry stages, but both were 4.19 times and 3.41 times higher, respectively, than those at the black berry stage, showing significant differences compared with the black fruit stage. The cohesiveness showed no significant change. The adhesiveness showed no significant difference between the green berry and red berry stages, but significant differences were observed among other developmental stages. The lignin content decreased significantly. The transcriptome sequencing identified 51 895 Unigenes, of them 35 395 were successfully annotated in databases such as the GO, KEGG, KOG, NR, NT and SwissProt. A total of 10 207 differentially expressed genes were identified, with more upregulated genes than downregulated ones. The KEGG pathway enrichment analysis revealed that the lignin biosynthesis pathway contained 45 differentially expressed genes, classified into three expression patterns: gradually upregulated (2 genes), upregulated first and then downregulated (19 genes), and gradually downregulated (24 genes). The third expression pattern was consistent with the trends in lignin content and texture quality indicators. The twenty-four differentially expressed genes were identified in the lignin biosynthesis pathway, and 10 were randomly selected for qRT-PCR experiments, confirming the reliability of the sequencing results. The redundancy analysis showed that lignin content had the highest positive correlation with fruit chewiness, followed by gumminess and hardness, with lignin contributing similarly to all three. The lignin content showed the smallest negative correlation with the berry adhesiveness, followed by the elasticity and cohesiveness. The CCR had the greatest influence on the lignin synthesis, followed by the CCoAOMT1, CCoAOMT2, PAL3, C3H and 4CL2, all of them positively contributed to the lignin synthesis. The 4CL2 had the greatest influence on berry hardness and gumminess, followed by the POD13, CCoAOMT1, CCoAOMT2, PAL3, C3H. CAD2 and POD12 negatively contributed to changes in berry hardness, gumminess and chewines, while the CAD2 positively contributed to changes in berry cohesiveness, adhesiveness and Springiness, followed by the CAD1, POD12 and POD15. The RDA results were consistent with the aforementioned gene expression patterns, confirming the reliability of the findings. [Conclusion] Based on the physiological indicators and transcriptomic data, it was inferred that the key genes in the lignin biosynthesis pathway, such as the PAL, C4H, 4CL, CCR, POD and CCoAOMT, would regulate lignin synthesis and participate in the ripening and softening process of the berries. These findings would provide theoretical references for improving mulberry ripening, preservation, and flavor.